Effect of a micronization method on the particle-size distribution and eluted phosphate-ion concentration for methane fermentation residue sludge. Issue 1 (31st December 2022) - Mori, Takamasa; Komiya, Yui; Yabe, Mitsuyasu
Abstract: Micronized methane fermentation residue sludge can be used as a liquid fertilizer because the micronized solid particles can be directly sprayed. Thus, the objective of this study was to clarify the effect of the micronization method on the particle-size distribution and eluted phosphate-ion concentration of sludge micronized by ultrasonication or ball milling. Although the average particle size in the sludge micronized by ball milling was ~15 µm smaller than that micronized by ultrasonication, many finer particles (<10 µm) were observed in the ultrasonication-micronized sludge. Compared with untreated sludge, the concentration of the eluted phosphate ions of ultrasonication-micronized sludge was almost 15% higher, whereas that of the ball-milled sludge changed insignificantly. These results indicate that the particle sizes in the ball-milled and ultrasonication-micronized sludge were different, resulting in different phosphate ion elution behavior. Thus, the particle size and phosphate ion concentration can be controlled by changing and/or combining micronization techniques and optimizing their operating conditions.